Autonomous learning of physics with the aid of a web site on electromagnetism - Legañoa Ferrá , Dra. C. María de los Ángeles; Hernández Wolpes , M. Sc. Manuel; Pérez Acosta , M.Sc. Lázaro (Transformación, 2024)
The paper argues the key role of ICT in autonomous learning of physics. The use of eb didactic materials in guiding autonomous learning in Cuban Higher Education is examined together with and account of autonomous learning guiding tasks in progress under the auspice of “Enrique José Varona” Center for Science of Education at the University of Camagüey. Likewise, the experience of the Physics Department in designing web didactic materials by means of Exelearning software is described. The standards being used in Physics courses and the features characterizing the Physics Web Didactics for Physics II are fully explained. The paper closes with the finding of the test given to a group of Electric Engineering second year students in 2012-2013 academic years.